Potential of Terminalia catappa Leaf Extract as Bioherbicide on Mikania micrantha Seed Germination - Herman; Syukran, Muhammad; Effendi, Arman (Jurnal Online Pertanian Tropik, 2022)
Mikania micrantha is a weed that is commonly found on agricultural land. Environmentally friendly weed control can be done using bioherbicides because the materials used come from nature. Terminalia catappa contains secondary metabolites so that its bioactive compounds can be used as weed control. This study aims to determine the total secondary metabolite compounds of Terminalia catappa leaves and their effect on Mikania micrantha seed germination. This study used a factorial Completely Randomized Design (CRD). The first factor is various types of solvents aquadest, ethanol and methanol. The second factor was the concentration of the extract application 30%, 50%, 70% and repeated 3 times so that there were 27 experimental units. Data were analyzed using analysis of variance if it had a significant effect, further tests were carried out using 5% BNJ. The results showed that the Terminalia catappa leaf extract with distilled aquadest of 70% was able to prevent the seeds from germinating while the methanol and ethanol solvent extracts were able to inhibit the germination of Mikania micrantha seeds at an application concentration of 30%.